Countrywide Spread of Community- and Hospital-Acquired Extended-Spectrum β-Lactamase (CTX-M-15)-Producing Enterobacteriaceae in Lebanon - Mokhbat, Jacques E. (2005)
A prospective study was carried out to assess the extent of carriage of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae at both hospital and community levels in Lebanon. A total of 1,442 fecal samples were collected from hospital-based patients and 58 from health care workers of six Lebanese tertiary care general hospitals located in different areas of Lebanon between January and March 2003. A total of 382 fecal samples were also collected from healthy subjects between April and June 2003. The samples analysis led to the identification of 118 strains as ESBL producers based on the synergistic effects between clavulanate and selected β-lactams (ceftazidime and cefotaxime). These strains were isolated from 72 subjects: 61 patients, 2 health care workers, and 9 healthy subjects. One representative strain per subject was selected, and a total of 72 nonduplicate ESBL producers, including a high majority of Escherichia coli (n = 56), Klebsiella pneumoniae (n = 9), Enterobacter cloacae (n = 6), and Citrobacter freundii (n = 1), were characterized. The molecular analysis revealed that the majority of the strains (83%) express CTX-M-15 ESBL (pI 8.6). SHV-5a ESBL (pI 8.2) was produced by 18% of the strains. DNA macrorestriction analysis of ESBL-producing E. coli presented 38 different genotypes, revealing the absence of clonal link among these strains. In addition to the fact that the present study highlights the emergence and the countrywide dissemination of CTX-M-15-producing E. coli in Lebanon, it represents the first report of an SHV-5a-producing C. freundii.